Pelaksanaan Opiumpacht: Monopoli Perdagangan Opium Melalui Perantara Bandar di Keresidenan Kediri, 1833-1900 - Ahmad Fathoni; Sarkawi B. Husain (Universitas Gadjah Mada, 2020)
The opium trade in Kediri Residency was monopolized by Dutch East Indies government. The problem discussed in this study regarding opium trade monopoly at Kediri Residency through bookie intermediary (opiumpachter) in 1833-1900. The methods used in this research is historical methods which includes heuristics, criticism, interpretation and historiography. The result showed that the opium trade monopoly through bookie intermediary (opiumpachter) in Kediri Residency included auction and distribution processions also the sale of raw opium to opium dealers. Generally, the opium trade in Kediri Residency was controlled by Chinese. They become intermediary traders who sell government opium to people in Kediri Residency. The high tax offer at opium auction in Kediri Residency gave high profits to the country. On the contrary, that puts a great deal of pressure on the opium port. The crisis which occurred at the end of the 19th century, caused a setback in the opium trade monopoly through bookie intermediary (opiumpachter) in Kediri Residency.